The relationship between platelet indices and residual SYNTAX score in patients with ST-segment elevation myocardial infarction - Yılmaz, Emre; Çamcı, Sencer (The European Research Journal, 2022)
Objectives: Our aim is to investigate the relationship between thrombocyte indices, which have previously been proven to be associated with many cardiovascular diseases and adverse events, and residual SYNTAX (SYNergy between percutaneous coronary interventionwith TAXus and cardiac surgery) score (rSS) in patients with ST-segment elevation myocardial infarction (STEMI). Methods: Our study included 534 patients who underwent primary percutaneous coronary intervention (PCI) for STEMI between January 2018 and June 2021. In our study, only patients who underwent infarct-related coronary artery revascularization in the index procedure were evaluated. First of all, patients were compared as two groups as low rSS (rSS ≤ 8) and high rSS (rSS > 8). Our definition of platelet indices includes mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (Pct), MPV to platelet ratio (MPVPR), platelet to lymphocyte ratio (PLR), and MPV to lymphocyte ratio (MPVLR). Results: The mean age of the study patients was 56.4 ± 10.3 years and 78.8% were male. The high rSS group had higher C-reactive protein, lower lymphocyte count, and significantly higher platelet indices other than PLR and MPV. Among the platelet indices, MPVLR was found to have the best correlation with rSS (r: 0.398, p < 0.001). MPVLR (AUC: 0.820, 95% CI: 0.701-0.899) was determined as the best diagnostic power index with 5.08 cut-off value in predicting high rSS with 88% sensitivity and 76% specificity (Youden index: 0.64). Age, right coronary artery involvement as culprit lesion, ejection fraction, diabetes mellitus and MPVLR (OR: 5.966 [2.489-8.413], p < 0.001) and PDW were identified as independent risk factors for predicting high rSS. Conclusions: In conclusion, increased MPVLR is associated with high rSS in STEMI patients. There is a significant positive correlation between MPVLR and rSS. MPVLR is an independent predictor of high rSS.